A WIRELESS DATALINK FOR A REMOTE CONTROLLED VEHICLE - MUSTAFA, HAMID ABDELMONIEM (Universiti Teknologi PETRONAS, 2007)
The objective of the project is to design and build awireless retrieval communication system that effectively transmits pertinent data using packets from aremote control vehicle to home base station. The rationale behind this project is to provide the user with information regarding the vehicle's proximity to other stationary objects, and surrounding temperature. ARF (Radio Frequency) transmitter and receiver will be used to transmit the data. The information gathered would be useful if the vehicle is used to explore unfamiliar' hazardous areas. The sensor's data acquisition for the transmitter is done using C-programming method, therefore the receiver PIC C programming is also completed in accordance to the transmitter data acquisition coding, and so as the Microsoft Visual Basic 6.0 interface.